Electromagnetic asymmetric films comprise metal organic frameworks derived porous carbon for absorption-dominated electromagnetic interference shielding. (15th March 2022) - Yuan, Mushan; Fei, Yang; Zhang, Haoruo; Qiu, Baowei; Shen, Lu; He, Xianru; Liang, Mei; Zhou, Shengtai; Chen, Yang; Zou, Huawei
Abstract: Electromagnetic interference (EMI) shielding materials with low thickness, outstanding mechanical flexibility, especially absorption-dominated high performance, continue to be a significant challenge. Herein, environmentally friendly and mechanically robust double-layered zeolitic imidazolate framework-67 (ZIF-67) derived porous carbon (C-ZIF67) and graphene nanoplate (GNP) films based on cellulose were fabricated via filtration-assisted self-assembly followed by hot-pressing. The optimum double-layered composite films with 0.1 mm thickness exhibit excellent mechanical properties with a tensile strength of 46.33 MPa, superior EMI shielding effectiveness (SE) of 50.5 dB in the X-band frequency range, with an absorption coefficient (A) of 0.87, and the absorption rate (SEA /SET ) is as high as 98.7%, benefiting from the highly efficient asymmetric conductive network structures and high-performance cellulose nanofibers (CNFs) matrix. The results indicated that "absorption-reflection-reabsorption" asymmetric double-layered functional network structured films possess excellent potential for applications in absorption-dominated EMI shielding fields. Graphical abstract: Image 1 Highlights: Double-layered asymmetric conductive network structure is designed for EMI shielding. The ultrathin film shows excellent EMI shielding effectiveness. It features an absorption-dominated EMI shielding mechanism. Cellulose nanofiber as a matrix for the C-ZIF67/GNP composite exhibits excellent mechanical properties and stability.